2013
DOI: 10.3171/2012.10.spine12271
|View full text |Cite
|
Sign up to set email alerts
|

Incidental durotomy during lumbar spine surgery: risk factors and anatomic locations

Abstract: Object Incidental durotomy (dural tear) is a common complication of lumbar spine surgery. The purpose of this study was to clarify the anatomical location of and the specific causative factors for incidental durotomy during primary lumbar spine surgery. Methods The authors retrospectively reviewed 1014 consecutive cases involving patients (412 women and 602 men; mean age 57 years; age range 11–97 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 19 publications
2
57
0
1
Order By: Relevance
“…In a retrospective study of 4,223 patients, Basques et al identified age >70 years, female sex, pulmonary disease, and preoperative hematocrit <36 as independent risk factors for intraoperative blood transfusion during lumbar fusion using a posterior approach (11). Similarly, in a retrospective study of 1,014 consecutive patients undergoing posterior lumbar fusion, Takahashi et al identified female sex, older age as well as underlying degenerative spondylolisthesis and juxtafacet cysts as risk factors for incidental durotomy (12). Given the higher risk of blood loss associated with posterior approaches by both our study and the literature (2,4,5), preoperative identification of these risk factors might sway surgical decision-making in favor of an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 4,223 patients, Basques et al identified age >70 years, female sex, pulmonary disease, and preoperative hematocrit <36 as independent risk factors for intraoperative blood transfusion during lumbar fusion using a posterior approach (11). Similarly, in a retrospective study of 1,014 consecutive patients undergoing posterior lumbar fusion, Takahashi et al identified female sex, older age as well as underlying degenerative spondylolisthesis and juxtafacet cysts as risk factors for incidental durotomy (12). Given the higher risk of blood loss associated with posterior approaches by both our study and the literature (2,4,5), preoperative identification of these risk factors might sway surgical decision-making in favor of an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…The risk increased with the age, and patients older than 84 years were 2.8 times more likely to have DT than those aged between 18 and 44 years. Age has been previously suggested to be a risk factor for DT [1,7,9]. Possible reasons for age as a risk factor include normal signs of DT group the patients with dural tear, nonDT group the patients without dural tear, WF weighted frequency aging such as narrowing the spinal canal, thicker ligamentum flavum, and osteophyte formation [22].…”
Section: Risk Factors For Dtmentioning
confidence: 99%
“…The reported incidence of DT for all spine surgeries is 1.6-10 % [1][2][3][4][5][6]. Previous studies have examined various risk factors for DT, which include age, patient gender, and experience level of the surgeon [1,2,[7][8][9][10][11][12]. DTs that cannot be closed, those that are not adequately closed, or those that are unrecognized may result in relevant cerebrospinal fluid leakage, which may cause postural headaches, vertigo, posterior neck pain, neck and/or stiffness, nausea, diplopia, photophobia, tinnitus, and blurred vision [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the occurrence of lumbar CSF leakage or pseudomeningocele following incidental durotomy is well described, 3,5,8,33,35,38 the senior author of the present study (A.J.) noted an alarming rate of symptomatic delayed lumbar spine pseudomeningoceles at our institution following lumbar decompression in the absence of intraoperative durotomy.…”
mentioning
confidence: 94%